Expression and Conservation of rol-genes in Rue, Ruta graveolens L., Plants Regeneration from Hairy Roots - Al-Mahdawi M. M.1, Al-Mallah M. K2 & Al-Ne’ma Q. Sh.3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this investigation hairy roots were induced on leave petioles of Ruta graveolens L. plants. These roots were white in color and negative geotropism. Paper electrophoresis of hairy roots extract resulted in the separation of black spots of agropine . These transformed roots were cured from Agrobacterium rhizogenes, some cultures of these roots were directly produced shoots, and other was orientated to produce callus. Subsequently this callus was capable to produce numerous regenerates. Both groups of shoots were rooted easily and successfully adapted to field conditions. Evidences of molecular biology assessment, including isolation and amplification(PCR) of DNA of each transformed tissues and plants coupled with DNA electrophoresis data proved the transfer of rol-genes, except rol B , in the regenerated plants.Conclusion: The genetic modified R. graveolens plants possess unique characters due to the conservation of rol-genes in their genomes.